Hydrological processes in glacierized high-altitude basins of the western Himalayas - Jeelani, G.; Shah, R.; Fryar, A.; Deshpande, R.; Mukherjee, Abhijit; Perrin, J. (2018)
Western Himalaya is a strategically important region, where the water resources are shared by China, India and Pakistan. The economy of the region is largely dependent on the water resources delivered by snow and glacier melt. The presented study used stable isotopes of water to further understand the basin-scale hydro-meteorological, hydrological and recharge processes in three high-altitude mountainous basins of the western Himalayas. The study provided new insights in understanding the dominant factors affecting the isotopic composition of the precipitation, snowpack, glacier melt, streams and springs. It was observed that elevation-dependent post-depositional processes and snowpack evolution resulted in the higher isotopic altitude gradient in snowpacks. The similar temporal trends of isotopic signals in rivers and karst springs reflect the rapid flow transfer due to karstification of the carbonate aquifers. The attenuation of the extreme isotopic input signal in karst springs appears to be due to the mixing of source waters with the underground karst reservoirs. Basin-wise, the input–output response demonstrates the vital role of winter precipitation in maintaining the perennial flow in streams and karst springs in the region. Isotopic data were also used to estimate the mean recharge altitude of the springs.